The Relationship Between Family Consensual Family Communication Patterns With Children's Languages In Children's Early Childhood Education Bintang Binaan Non-Formal Education Unit 1 Padang City - Marsetiani, Elvina; Solfema, Solfema (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
This research is motivated by the low consensual type of family communication patterns in families in early childhood education of the fostered non-formal education unit in the learning activities area of Padang City. This is mainly due to the modesty of language that is not well applied by parents. This study aims to improve the pattern of consensual type family communication with the child's language politeness. This type of research is quantitative correlational with the population is the parents of students enrolled in early childhood education of the fostered non-formal education unit in the learning activities area of the city of Padang, amounting to 43 people. Sampling using stratified random sampling technique. The research sample was taken as many as 75%, totaling 33 people. Data collection using questionnaire techniques, while data collection tools use questionnaires in the form of statement items, and analyzed using percentages and product moments. The results of this study indicate that: (1) the consensual type of family communication patterns are categorized as unsatisfactory, (2) the politeness of children's language in early childhood education The fostered non-formal education unit in learning activities in Region 1 of Padang is categorized as impolite, and there is a relationship which is significant between consensual type family communication patterns with the politeness of children's language in early childhood education of the fostered non-formal education unit in the learning activities area of Padang City. The expectation of this research is that parents can use consensual type of communication patterns in the family to improve children's language politeness so that they develop properly